Visualization of lignification in flax stem cell walls with novel click-compatible monolignol analogs - Yao, Lan; Wang, Rui; Yoo, Chang Geun; Zhang, Yuhang; Meng, Xianzhi; Liu, Wei; Ragauskas, Arthur J.; Yang, Haitao (Frontiers in Plant Science, 2024)
As an essential part of plant cell walls, lignin provides mechanical support for plant growth, enhances water transport, and helps to defend against pathogens. As the most abundant natural aromatic-based renewable resource on earth, its biosynthesis has always been a research focus, and it is still under study nowadays. In this study, the p-coumaryl alcohol analog (H ALK ) and the coniferyl alcohol analog (G ALK ) containing an alkyne group at the ortho position were synthesized and applied to lignification in vivo and in vitro. The incorporation of these novel lignin monomers was observed via fluorescence imaging. It was found that the two monolignol analogs could be incorporated in dehydrogenated polymers (DHPs) in vitro and in flax cell walls in vivo. The results showed that as the cultivation time and precursor concentration varied, the deposition of H and G-type lignin exhibited differences in deposition mode. At the subcellular scale, the deposited lignin first appears in the cell corner and the middle lamella, and then gradually appears on the cell walls. Furthermore, lignin was also found in bast fiber. It was demonstrated that these new molecules could provide high-resolution localization of lignin during polymerization.